Characterization of furathiocarb metabolism in in-vitro human liver microsomes and recombinant cytochrome P450 enzymes - Khaled Abass; Petri Reponen; Walaa F. Alsanie; Arja Rautio; Olavi Pelkonen (Toxicology Reports, 2022)
Furathiocarb is a carbamate insecticide detected in ecosystems. Its main metabolite carbofuran has been alluded to affect birth outcomes and disturb hormone levels in humans. The metabolism of furathiocarb in humans has not been characterized. The metabolism studies were performed using hepatic microsomes from ten donors and fifteen human cDNA-expressed CYPs. The initial screening and identification of the metabolites were performed by LC-TOF. Quantiﬁcations and fragmentations were performed by LC/MS-MS. Furathiocarb was metabolized to eight phase I metabolites via two general pathways, carbofuran metabolic pathway and furathiocarb oxidation pathway. Six metabolites in the carbofuran metabolic pathway (carbofuran, 3-hydroxycarbofuran, 3-ketocarbofuran, 3-keto-7-phenolcarbofuran, 3-hydroxy-7-phenolcarbofuran, and 7-phenolcarbofuran) were identified with the help of authentic standards. The two unidentiﬁed metabolites in the furathiocarb oxidation pathway are probably hydroxylated and sulfoxidated derivatives of furathiocarb. The carbofuran metabolic pathway was more predominant than the furathiocarb oxidation pathway, ratios ranged from 24- to 115-fold in a 10-donor panel of hepatic microsomes. On the basis of recombinant CYP studies, the carbofuran pathway was dominated by CYP3A4 (95.9%); contributions by CYP1A2 (1.3%) and CYP2B6 (2.0%) were minor. The minor furathiocarb oxidation pathway was catalyzed by CYP2C19 and CYP2D6 (hydroxylated/sulfoxidated metabolite A) and by CYP3A5, CYP3A4 and CYP2A6 (metabolite B). High and significant correlation between carbofuran metabolic pathway and CYP3A4 marker activities (midazolam-1'-hydroxylation and omeprazole-sulfoxidation) were observed. Ketoconazole, a CYP3A4-inhibitor, inhibited the carbofuran pathway by 32–86% and hydroxylated/sulfoxidated metabolite-B formations by 41–62%. The data suggest that in humans, the carbofuran metabolic pathway is dominant, and CYP3A4 is the major enzyme involved. These results provide useful scientific information for furathiocarb risk assessment in humans.